A comparison between short GRB afterglows and kilonova AT2017gfo: shedding light on kilonovae properties. Issue 3 (19th February 2020) - Rossi, A; Stratta, G; Maiorano, E; Spighi, D; Masetti, N; Palazzi, E; Gardini, A; Melandri, A; Nicastro, L; Pian, E; Branchesi, M; Dadina, M; et al.
ABSTRACT: Multimessenger astronomy received a great boost following the discovery of kilonova (KN) AT2017gfo, the optical counterpart of the gravitational wave source GW170817 associated with the short gamma-ray burst GRB 170817A. AT2017gfo was the first KN that could be extensively monitored in time using both photometry and spectroscopy. Previously, only few candidates have been observed against the glare of short GRB afterglows. In this work, we aim to search the fingerprints of AT2017gfo-like KN emissions in the optical/NIR light curves of 39 short GRBs with known redshift. For the first time, our results allow us to study separately the range of luminosity of the blue and red components of AT2017gfo-like kilonovae in short GRBs. In particular, the red component is similar in luminosity to AT2017gfo, while the blue KN can be more than 10 times brighter. Finally, we exclude a KN as luminous as AT2017gfo in GRBs 050509B and 061201.